The time, than the resource of the managerial activity - Bácsné Bába, Éva (Acta Agraria Debreceniensis, 2009)
The role of the time factor in management is increasing. Change directs attention to the time factor from the point of view of the organisation, and management does the same from that ofthe person. I examined the time management practice of managers of organisations related to agribusiness, and the reaction time characterising the adaption ability of the organisations through a questionnaire survey. I analysed the collected data with scientifically established statistical methods.During studying resources I analysed the time factor from two aspects. On the one hand, I wanted to know what role time has in managers’ opinions in increasing company efficiency andperformance. On the other hand, I asked them how much they consider this resource to be expandable.